Genitoplasty in newborn females with adrenogenital syndrome: Focus on the reconstruction technique and its outcomes. Issue 2 (April 2018) - Waterloos, Marjan; Claeys, Tom; Sempels, Maxime; Van Laecke, Erik; Hoebeke, Piet; Spinoit, Anne-Françoise
Summary: The adrenogenital syndrome is an autosomal recessive disorder in which an enzyme defect in the steroid pathway leads to excessive prenatal exposure of androgens. In the female fetus, masculinization of the external genitalia is observed. Surgery aims for functional and aesthetical reconstruction. Many techniques have been described. A video of our modified pull-through reconstruction technique is hereby presented. A retrospective descriptive database was created with patients who underwent genitoplasty for a CAH-associated genital condition. A video demonstrating the reconstructive technique was recorded while operating on a 9-month-old girl. Prior to surgery a cystoscopy is performed to evaluate the length of the urogenital sinus. Surgery starts with creating a reversed U-flap, after which the urogenital sinus is mobilized. The corpora cavernosa are released and the neurovascular bundle is isolated. To create vaginal space the urogenital sinus is subsequently separated. The vaginal introitus is anchored to the perineal skin flap. Labia minora are created by splitting the preputial skin. Finally excessive skin tissue is resected. Twenty-two female patients underwent reconstructive surgery for the adrenogenital syndrome in a tertiary referral centre over 16 years. Median age at surgery was 3 months (0–190). Median follow-up was 36 months (0–108) after surgery. A good functional and aesthetical outcome was observed. The modified pull-through technique, illustrated by this video, provided satisfactory results with a low complication rate. Follow-up until adulthood is needed to evaluate long-term outcomes.